Educational Service Model for The Special Intelligence and Special Talents of Students: Literature Review - Murniviyanti, Liza (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
Children with special intelligence and special talents are those who have above average intelligence, have faster memory and comprehension abilities compared to their friends. Thus, children in this category have many achievements; apart from that they also have the characteristics of self-confidence and perfectionism. Children with special intelligence and special talents certainly have intelligence or ability in one area that stands out the most. This research uses a literature review or literature review design, by examining 18 articles consisting of national and international articles related to service models for students with special intelligence and special talents. From the articles, it was found that the education service model for special intelligent children and special talents in several countries is the inclusive and accelerated model.